Complete mitochondrial DNA sequence of yellow-legged buttonquail (Turnix tanki) - Xue Gou; Shize Li; Cheng Wang; Han Fan; Caichun Peng; Canshi Hu; Mingming Zhang; Haijun Su (Mitochondrial DNA. Part B. Resources, 2021)
The Yellow-legged Buttonquail Turnix tanki is a species of the genus Turnix, which belongs to the order Charadriiformes. It is distributed across almost all of China. The International Union for Conservation of Nature has assessed the bird’s conservation status as ‘Least Concern (LC).’ We sequenced the complete mitogenome of T. tanki and examined its phylogenetic relationship with other charadriiformes species. The mitochondrial DNA is packaged in a compact 17,620 base pair circular molecule with A + T content of 57.90%. It contains 37 typical mitochondrial genes, including 13 protein-coding genes, two rRNAs and 22 tRNAs, and two non-coding regions. We reconstructed a phylogenetic tree based on mitogenome sequences of five Turnicidae species and one outgroup. Phylogenetic analysis indicated that T. tanki is a sister to T. suscitator.